Regulatory T cells as well as IL-10 are reduced in the skin of patients with dermatitis herpetiformis. Issue 1 (January 2015) - Antiga, Emiliano; Quaglino, Pietro; Pierini, Ilaria; Volpi, Walter; Lami, Gabriele; Bianchi, Beatrice; Del Bianco, Elena; Renzi, Daniela; Baroni, Gianna; Novelli, Mauro; Ponti, Renata; Papini, Manuela; et al.
Highlights Tregs and IL-10 are reduced in the skin of patients with dermatitis herpetiformis (DH). Reduction of Tregs may lead to a defective suppressive function in DH lesions. No difference in Tregs can be found in the duodenum and blood of patients with DH and celiac disease.